2022
DOI: 10.1002/bies.202100288
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4: A trigger of pathological RhoA activation in neurological disease

Abstract: Transient receptor potential vanilloid 4 (TRPV4), a member of the TRP superfamily, is a broadly expressed, cell surface-localized cation channel that is activated by a variety of environmental stimuli. Importantly, TRPV4 has been increasingly implicated in the regulation of cellular morphology. Here we propose that TRPV4 and the cytoskeletal remodeling small GTPase RhoA together constitute an environmentally sensitive signaling complex that contributes to pathological cell cytoskeletal alterations during neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 116 publications
(166 reference statements)
0
16
0
Order By: Relevance
“…45 As a cell surface-localized ion channel, TRPV4 has been increasingly implicated in the regulation of cellular morphology that is associated with the cytoskeletal remodeling small GTPase RhoA. 46 Our data showed that mechanosensitive TRPV4 channels on the SMC membrane regulated the contraction of SMCs that is closely associated with actin cytoskeleton stress fibers and RhoA phosphorylation, suggesting that it senses intracellular traction force.…”
Section: Original Articlementioning
confidence: 63%
“…45 As a cell surface-localized ion channel, TRPV4 has been increasingly implicated in the regulation of cellular morphology that is associated with the cytoskeletal remodeling small GTPase RhoA. 46 Our data showed that mechanosensitive TRPV4 channels on the SMC membrane regulated the contraction of SMCs that is closely associated with actin cytoskeleton stress fibers and RhoA phosphorylation, suggesting that it senses intracellular traction force.…”
Section: Original Articlementioning
confidence: 63%
“…Although our current studies focus on the effect of RhoA on TRPV4 function, conversely, TRPV4 activity can modulate RhoA unbinding and release 22 . Once TRPV4 is activated, the membrane-bound RhoA is released to regulate cytoskeleton dynamics upon activation by TRPV4-mediated calcium influx 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The influx of Ca 2+ is induced by some ion channels such as Piezo-1, transient receptor potential vanilloid 4 (TRPV4) and N -methyl- D -aspartate (NMDA) receptor. Interestingly, Piezo-1 and TRPV4 are activated by mechanical forces such as shear stress and the tension of the plasma membrane; Piezo-1 acts as an upstream regulator for TRPV4 and induces a transient Ca 2+ influx while TRPV4 induces a sustained Ca 2+ influx and activates associated RhoA [ 114 , 115 ]. Activation of TRPV4 is inhibited by phosphatidylinositol 4,5-bisphosphate (PIP 2 ) but the activation of Gα q/11 subunits convert PIP 2 to inositol trisphosphate (IP 3 ) [ 116 , 117 ].…”
Section: The Regulatory Mechanisms Of Cldn-5 By Junctional Proteins A...mentioning
confidence: 99%